"I'll Do Business with Anyone": Arab Teachers in Jewish Schools as a Disruptive Innovation. Issue 3 (1st December 2020) - Erlich, Rakefet Ron; Gindi, Shahar; Hisherik, Michal
Abstract: Given the surplus of Arab teachers and the shortage of Jewish teachers in Israel, the government has adopted the policy of employing Arab teachers in Jewish schools, contrary to the dominant nationalistic agenda. We argue that this low-cost solution meets the criteria for disruptive innovation in that it flies under the radar and has the potential to proliferate and change the existing social order. Through surveys and interviews with boundary-crossing Arab teachers, this article finds that teachers circumvent power structures in three social fields. In the Arab community, work in Jewish schools helps teachers bypass nepotism and provides a new path for upward mobility. In the education system, boundary-crossing teachers disrupt segregation. And at the state level, this innovation may improve Jewish-Arab relations.